151k views
4 votes
Solve for y using Proportion.

y/p-q = y/p+q



A.) 0


B.) y/q


C.) 1/2q

2 Answers

1 vote

Answer:

The answer would be A) 0

Explanation:

In order to find this, cross multiply to solve.

y/p-q = y/p+q

y(p + q) = y(p - q)

yp + yq = yp - yq -----> Subtract yp from both sides

yq = -yq -----> Add yq to both sides

2yq = 0 ------> divide by 2q

y = 0

User Jonas W
by
4.3k points
6 votes

Answer:

The correct answer is option A.

Explanation:


(y)/(p-q)=(y)/(p+q)

Solving by proportions :


a:b:: c:d


ad=bc

So,


y* (p+q)=y* (p-q)


p+q=p-q


p-p=-q-q


0=-2q

q = 0

Hence, the correct answer is option A.

User Nidhi
by
5.2k points